Performance of Growth in Tilapia Fish in Polyculture System - Maimunah, Yunita (Journal of Food and Life Sciences, 2020)
Tilapia growth in pond using polyculture system is higher than tilapia cultured in monoculture system. Employing water column for fish and prawn culture to obtained higher production yield. This research using experimental descriptional method and data were analyzed using independent t-test, comparing monoculture and polyculture of Tilapia growth performance. Specific growth rate of polyculture Tilapia at 4.46%/BW/day is higher than monoculture fish at 4.80%/BW/day. FCR comparisonÂ  were 1,1 and 1.17 for polyculture and monoculture respectively. Water quality treatments were at optimal range for Tilapia growth at 26-30C; 7,34-8,36; and 5,3-8,8Â  ppm for temperature, pH dan dissolved oxygen, respectively.